Broad protective immune responses elicited by bacterium-like particle-based intranasal pneumococcal particle vaccine displaying PspA2 and PspA4 fragments. Issue 2 (1st February 2019) - Lu, Jingcai; Guo, Jieshi; Wang, Dandan; Yu, Jinfei; Gu, Tiejun; Jiang, Chunlai; Kong, Wei; Wu, Yongge
ABSTRACT: Streptococcus pneumoniae is an infectious pathogen mainly infecting host bodies through the respiratory system. An effective pneumococcal vaccine would be targeted to the mucosa and provide not only protection against invasive infection but also against colonization in the respiratory system. In the present work, we applied bacterium-like particles (BLPs) as an adjuvant for the development of a PspA mucosal vaccine, in which the PspA protein was displayed on the surface of BLPs. Intranasal immunization with the PspA-BLP pneumococcal vaccine, comprised of PspA2 from pneumococcal family 1 and PspA4 from pneumococcal family 2, not only induced a high level of serum IgG antibodies but also a high level of mucosal SIgA antibodies. Analysis of binding of serum antibodies to intact bacteria showed a broad coverage of binding to pneumococcal strains expressing PspA from clade 1 to 5. Immunization with the PspA-BLP vaccine conferred protection against fatal intranasal challenge with both PspA family 1 and family 2 pneumococcal strains regardless of serotype. Therefore, the PspA-BLP pneumococcal vaccine was demonstrated to be a promising strategy for mucosal immunization to enhance both systemic and mucosal immune responses.